2022
DOI: 10.3390/antiox11122341
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Carnosol on Renal Interstitial Fibrosis in a Murine Model of Unilateral Ureteral Obstruction

Abstract: Renal fibrosis is a common feature of chronic kidney disease and is a promising therapeutic target. However, there is still limited treatment for renal fibrosis, so the development of new anti-fibrotic agents is urgently needed. Accumulating evidence suggest that oxidative stress and endoplasmic reticulum (ER) stress play a critical role in renal fibrosis. Carnosol (CS) is a bioactive diterpene compound present in rosemary plants and has potent antioxidant and anti-inflammatory properties. In this study, we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 91 publications
4
17
0
Order By: Relevance
“…Our data validated that CAD could restore the activity of crucial antioxidant enzymes to block oxidative stress in both I/R and UUO models. In addition, the influential outcome of SOD1, catalase, and SOD2 on alleviating acute and chronic injuries was authenticated as well in our reports and others. , …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our data validated that CAD could restore the activity of crucial antioxidant enzymes to block oxidative stress in both I/R and UUO models. In addition, the influential outcome of SOD1, catalase, and SOD2 on alleviating acute and chronic injuries was authenticated as well in our reports and others. , …”
Section: Discussionsupporting
confidence: 93%
“…In agreement with tissue staining, specific kidney injury markers such as BUN and Cr also experienced a noticeable decline in the UUO + CAD group (Figure H,I). Additionally, positive indicators of fibrosis degree including collagen I, collagen III, fibronectin, and α-SMA went through the conspicuous upregulation in the UUO surgery . Nevertheless, CAD delivery by gavage reversed the alteration trend of protein expression in those markers (Figure J).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, hesperetin treatment alleviated LPS-induced renal tubular structural damages (tubular injury score: LPS, 2.4 ± 0.3 vs. LPS+Hes, 1.1 ± 0.2, p < 0.01; Figure 1 B,C). Next, the brush border of proximal tubules was visualized using a fluorescein isothiocyanate (FITC)-conjugated lotus tetragonolobus lectin (LTL) to examine the brush border loss [ 26 , 27 ]. Immunofluorescence (IF) staining revealed that LPS injection reduced the percentage of the LTL-stained area, but this change was mitigated by hesperetin (LPS, 4.1 ± 1.0% vs. LPS+Hes, 9.1 ± 1.4%, p < 0.05; Figure 1 D,E).…”
Section: Resultsmentioning
confidence: 99%